Assess The Effect Bridges Constructed On Hydraulic Behavior Of The River Within The City (Case Study: River City Chai Urmia) - Elnaz Asadi nia; Mirali Mohammadi; Fatemeh Vojudi Mehrabani (مهندسی و مدیریت ساخت)
Among the ever-increasing human advances, activities such as bridges have a significant role to play in the hydrostatic behavior of rivers as the main source of life. In the present study, with the definition of four scenarios, the effect of the constructed bridges on the hydraulic behavior of the Shahr-e-Chahi Urmia River using Artificial Intelligence (GEP) and the integration of HEC-RAS and HEC-GEORAS software is discussed. In the first scenario, the presence or absence of structures does not have much effect on river flow capacity and water level levels. Investigations in the second scenario confirm the ability of structures in flood flow with the return periods of 2, 5, 10, 25, 50 and 100. In the third and fourth scenarios, the water surface profile is simulated in different flows, and the capacity of each of the existing bridges in the route is equal to: 650 cubic meters per second (bridge Jounoslou), 1200 m 3 / s (bridge bridge) and 750 The cubic meter per second (bridge of justice) is achieved.